Uji Aktivitas Analgetik Ekstrak Batang Karamunting (Rhodomyrtus tomentosa) terhadap Tikus Jantan Galur Wistar - Rika Arfiana Safitri; Mamik Ponco Rahayu; Gunawan Pamudji Widodo (Jurnal Surya Medika (JSM), 2022)
Pain is only a symptom and a mechanism in the body that serves as a danger signal about a disturbance in the tissue such as inflammation, infection, or muscle spasms. This study aims to determine the effect of the analgesic effect of the ethanol extract of the karamunting stem. Karamunting stems were extracted by the maceration method using 96% ethanol as solvent. Each analgesic test was divided into five groups, namely a negative control group (CMC Na), a positive control group (Tramadol), a karamunting stem extract test group (a dose of 100 mg/kg BW, 200 mg/Kg BW, and 400 mg/Kg BB). Analgesic test using Tail flick method. Data analysis used the Shapiro-Wilk test and then continued with the one-way ANOVA test. The results showed that the ethanol extract of the karamunting stem could provide an analgesic effect at a dose of 200 mg/Kg BW.